Kinetic Study for Janus Green Dye Adsorption from Aqueous Solutions Using Iraqi Bauxite Clay and its Composite - Abbas Jumaa Sahal; Ahmed Mohammed Abbas (Wasit Journal for Pure Sciences, 2023)
Clays are considered important natural materials in the field of water purification, including bauxite clay (BAU) and its prepared and activated composite (BAU/CMC-AC) with carboxymethyl cellulose polymer. The ad-sorbent surfaces are characterized by FTIR and XRD techniques. The adsorp-tion of green janus (JG) from an aqueous solution with bauxite and its compo-site were studied under the influence of different conditions of the weight and size of adsorbed surface particles, contact time and temperature. The results were found to be: contact time (90, 45) min for maximum quantity adsorbed of (JG) dye on bauxite and its composite respectively. The experimental data were tested on pseudo 1st- and 2nd-order kinetic models. It was shown to apply more with the pseudo-2nd order kinetic model for both adsorbents. It also showed that the highest removal percentage were (78%, 88.5 %) for the bauxite surface and its composite (BAU, BAU/CMC-AC) at the preferred temperature